2019
DOI: 10.1016/j.jcf.2019.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Puberty in cystic fibrosis

Abstract: Historically, delayed puberty was considered a common clinical feature of cystic fibrosis (CF). More recent reports have documented normal pubertal progression in the majority of individuals with CF. However, youth with more severe disease are still at risk for delayed puberty. Careful evaluation of pubertal development in children and adolescents with CF is important as pubertal timing impacts linear growth, bone mineral accrual, body image and psychosocial wellbeing, all of which can also be impacted directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Delayed puberty is defined as absence of secondary sexual characteristics by age 13 for females and 14 for males [57] . Pubertal delay is estimated to occur in 20–60% of CF patients in older studies, while more recent studies demonstrate no difference in puberty timing between CF patients and controls [58] , [59] . Among the general population, pubertal delay is associated with delay to achieve peak bone mass and lower BMD at age 25 years [60] , [61] .…”
Section: Nonpharmacological Therapymentioning
confidence: 96%
“…Delayed puberty is defined as absence of secondary sexual characteristics by age 13 for females and 14 for males [57] . Pubertal delay is estimated to occur in 20–60% of CF patients in older studies, while more recent studies demonstrate no difference in puberty timing between CF patients and controls [58] , [59] . Among the general population, pubertal delay is associated with delay to achieve peak bone mass and lower BMD at age 25 years [60] , [61] .…”
Section: Nonpharmacological Therapymentioning
confidence: 96%
“…When assessing growth as the patient nears the age of pubertal onset, assessment of pubertal status with Tanner staging is indicated, and is concerning for pubertal delay if there are no signs of puberty by age 12À13 years in girls or age 14 years in boys. The reader is referred to the Delayed Puberty [83], for further details. Bone age x-ray of the left hand may assist in quantifying the degree of bone maturation and/or pubertal delay, if present.…”
Section: Diagnostic Work Upmentioning
confidence: 99%
“…It is important to note that youth with more severe lung disease, poorly controlled CF‐related diabetes (CFRD) and CF‐related liver disease (CFRLD) are still at risk for malnutrition and may remain at risk for delayed puberty, and therefore, require close monitoring to ensure growth and pubertal development. 18 …”
Section: Introductionmentioning
confidence: 99%
“…20 Finally, it is also important to note that emotional changes associated with puberty can be challenging for all adolescents and, therefore, medical and psychosocial guidance is crucial in the prepubertal and pubertal period for a healthy transition to adulthood. 18,21 In this context, adolescents are commonly focused on their appearance and body image. An Australian survey found that symptoms (coughing, flatulence, steatorrhea, and digital clubbing) and signs (pubertal delay, short stature, and low body mass) seen commonly in CF were extremely distressing and isolating for adolescents, especially if the signs and symptoms caused visible differences compared to their peers.…”
mentioning
confidence: 99%